REARING OF CARRIED OVER CARP SEED IN PEN ENCLOSURE IN A CLOSED FLOODPLAIN WETLAND OF ASSAM - BHATTACHARJYA, B. K.; YENGKOKPAM, SONA; GOGOI, PRANAB; SARMA, K. K.; DEBNATH, DIPESH (Journal of the Inland Fisheries Society of India, 2021)
Results of a pen aquaculture experiment carried out during 2009 for rearing carp fingerlings in Damal beel, (a closed type floodplain wetland), Morigaon district, Assam are described. A rectangular pen of 741 m2 constructed using netlined split-bamboo screens was stocked with carried over fingerlings of Indian major and exotic carps @ 5 No. m-2. Average stocking size were 14.2 cm/ 41.9 g for Catla catla, 9. 6 cm/ 19.3 g for Labeo rohita, 10.2 cm/ 9.4 g forCirrhinus mrigala, 15.3 cm/ 45.7 g for Ctenopharyngodon idella and 17.2 cm/ 46.0 g for Hypophthalmichthys molitrix. Stocked fishes were fed with rice polish and mustard oil cake mixture (1:1) fortified with vitamin-mineral premix (1%) @ 5% of body weight. Water in the pen was characterized by favourable temperatures (23.0-33.9 oC), clear water (Secchi disc visibility 48-50 cm), alkaline pH (7.1-8.2), optimal dissolved oxygen (7.0-7.5 mg l-1), undetectable free carbon dioxide and moderate total alkalinity (22-23 mg l-1). Seed were reared for 70 days before releasing them in the beel. Highest specific growth rate was observed in silver carp (2.40) followed by mrigal (2.11), grass carp (1.51), rohu (1.43) whereas catla recorded the lowest rate (0.80). Estimated fish production in the pen was 1529 kg ha-1 in 70 days. The benefit-cost ratio was 1.8 showing that rearing carried over carp seed in the pen was economically viable.Key words: Pen aquaculture, floodplain wetland, Damal beel, Assam, exotic carps.